1976
DOI: 10.1002/dev.420090406
|View full text |Cite
|
Sign up to set email alerts
|

The behavioral effects of prenatal hypoxia in the rat

Abstract: Pregnant rats were exposed to an oxygen depleted atmosphere (13% oxygen in nitrogen) at normal pressure in 2-hr daily sessions extending over approximately the last 14 days of pregnancy. Their progeny were compared with control progeny in terms of age of eye-opening, open-field behavior, and Hebb-Williams maze problem solving ability. The groups were not distinguishable by their performance in the open-field, but the experimental animals opened their eyes significantly earlier and made significantly more error… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
6
0

Year Published

1980
1980
2001
2001

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(8 citation statements)
references
References 16 publications
2
6
0
Order By: Relevance
“…By contrast, mild hypoxia produced none of these anomalies and did not affect acquisition of shock avoidance, as evidenced by the insignificant Days x Treatment interaction in the analysis of the number of shocks received. That Group N litters differed insignificantly from others on measures of emotional behavior is consistent with the conclusions of McCullough and Blackman (1976) using similarly mild hypoxia. Consequently, the debilitation associated with the Group E treatment probably resulted from both hypoxia and otic barotrauma.…”
Section: Discussionsupporting
confidence: 82%
“…By contrast, mild hypoxia produced none of these anomalies and did not affect acquisition of shock avoidance, as evidenced by the insignificant Days x Treatment interaction in the analysis of the number of shocks received. That Group N litters differed insignificantly from others on measures of emotional behavior is consistent with the conclusions of McCullough and Blackman (1976) using similarly mild hypoxia. Consequently, the debilitation associated with the Group E treatment probably resulted from both hypoxia and otic barotrauma.…”
Section: Discussionsupporting
confidence: 82%
“…Antenatal maternal intermittent hypoxia led to the increased locomotor activity of 19-day-old male rats but not female rats [10]. On the other hand, McCullough and Blackman [24] showed that there were no significant differences in open-field behavior of both female and male rats tested on day 55 following chronic intermittent prenatal hypoxia. The discrepant results may be due to the degree and period of the insult used in those experimental conditions.…”
Section: Discussionmentioning
confidence: 96%
“…It is possible that this sexual difference in behavior might be due to some functional differences of sex. Numerous studies have demonstrated neurological sequelae of hypoxic insult during the perinatal period, such as learning disabilities, motor disturbances and behavioral alterations [10,12,23,24]. Neurotransmitter systems are involved in the regulation of locomotor activity, which develop differ- female) compared to control pups (c: male, d: female) at PD7.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, lack of oxygen may result in damage of the central nervous system with consequent aberrations of the behavior of the offspring later in life (3,6). Recently we demonstrated by means of pulse-oximetry in fetal rats that the oxygen transport by the placenta was seriously diminished after treatment of the mother with endotoxin as low as 0.2 p,g on day 19 of pregnancy (13).…”
Section: Ratmentioning
confidence: 99%